Fibroin nanofibers production by electrospinning method - YÜKSEK, METİN (SCIENTIFIC TECHNICAL RESEARCH COUNCIL TURKEY-TUBITAK, 2021)
Silk fibroin, which has many characteristic properties such as low inflammation reaction, biodegradation, suppleness, good antithrombogenic details, biocompatibility and high tensile strength is a very good candidate for biomedical applications. Electrospinning procures high surface area, porous, nanofiber dimension fiber generation, which is a plain method. An experimental study was carried out to produce nanofiber structure from silk fibroin by electrospinning and the electrospinning parameters for the spinning of uniform, continuous and silk fibroin fibers were optimized. As a result, the effect of variables of concentration, distance and applied voltage on the strength, thickness, surface structure, fiber diameter of nanomaterial was investigated. Then, in vitro cell viability of the silk fibroin mat was analyzed. It was seen that the strength, mat thickness, and fiber diameter increased with solution concentration rise. It was found that the values of the fiber diameter and tensile strength decreased with increasing distance. It was determined that the effect of distance varies depending on the concentration in the mat thicknesses. The tensile strength was affected inversely proportional the applied voltage rises and distance. It was found that the fiber diameter values decreased together with increasing applied voltage. At cell viability of silk fibroin mat was occurred high cell viability after 24 h, but it was obtained low cell viability at the 48th h.
Keywords: Electrospinning method; silk fibroin; nano material; MORI SILK FIBROIN; SCAFFOLDS; FABRICATION; FIBERS